2014
DOI: 10.1109/tap.2013.2293336
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Microwave Constrained Focusing for Patient-Specific Breast Cancer Hyperthermia: A Robustness Assessment

Abstract: In this paper, we address the problem of microwave hyperthermia. In particular, we first introduce simple tools to understand the relationship between thermal and electromagnetic power focusing. Then, we assess the electromagnetic and thermal performances of a recently proposed strategy to design array applicators. Contrary to common approaches, such a strategy allows a punctual control of power deposition, which is crucial for effective treatment planning. With respect to breast cancer hyperthermia, we analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
52
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(53 citation statements)
references
References 28 publications
(51 reference statements)
1
52
0
Order By: Relevance
“…Previous studies had shown that microwave hyperthermia is a promising noninvasive treatment for breast cancer [5]- [10]. The performance of ultra-wideband and narrowband microwave hyperthermia based on beam forming was investigated theoretically in [11].…”
mentioning
confidence: 99%
“…Previous studies had shown that microwave hyperthermia is a promising noninvasive treatment for breast cancer [5]- [10]. The performance of ultra-wideband and narrowband microwave hyperthermia based on beam forming was investigated theoretically in [11].…”
mentioning
confidence: 99%
“…However, one of the persisting challenges of breast cancer hyperthermia is the requirement to focus the microwave power at the target while preventing auxiliary foci in surrounding tissues. Many studies are dedicated to investigating different techniques for focusing microwave hyperthermia for non-invasive treatment of the breast [34,49,52,62,64,65,[69][70][71][73][74][75][76][77][78]. These studies present interesting results of focusing microwave power for breast cancer treatment, however, there are several drawbacks that need to be solved.…”
Section: Existing Non-invasive Approaches For Localized Heating Tumoumentioning
confidence: 99%
“…Also conducted in a 2D environment, the recent study in [75] has introduced an optimization technique to focus the microwave power inside the breast phantom. The approach exploits the Green function for solving the bio-heat equation and uses the optimal constrained power focusing method to design the antenna array.…”
Section: Two-dimensional (2d) Computational Techniquesmentioning
confidence: 99%
See 2 more Smart Citations